Cyberbiosecurity: A New Perspective on Protecting U.S. Food and Agricultural System - Duncan, Susan E.; Reinhard, Robert; Williams, Robert C.; Ramsey, Ford; Thomason, Wade; Lee, Kiho; Dudek, Nancy; Mostaghimi, Saied; Colbert, Edward; Murch, Randall (Frontiers in Bioengineering and Biotechnology, 2019)
Our national data and infrastructure security issues affecting the ‘bioeconomy’ are evolving rapidly. Simultaneously, the conversation about cybersecurity of the U.S. food and agricultural system (cyberbiosecurity) is incomplete and disjointed. The food and agricultural production sectors influence over 20% of the nation’s economy ($6.7T) and 15% of U.S. employment (43.3M jobs). The food and agricultural sectors are immensely diverse and they require advanced technologies and efficiencies that rely on computer technologies, big data, cloud-based data storage, and internet accessibility. There is a critical need to safeguard the cyberbiosecurity of our bioeconomy, but currently protections are minimal and do not broadly exist across the food and agricultural system. Using the food safety management Hazard Analysis Critical Control Point system concept as an introductory point of reference, we identify important features in broad food and agricultural production and food systems: dairy, food animals, row crops, fruits and vegetables, and environmental resources (water). This analysis explores the relevant concepts of cyberbiosecurity from food production to the end product user (such as the consumer) and considers the integration of diverse transportation, supplier and retailer networks. We describe common challenges and unique barriers across these systems and recommend solutions to advance the role of cyberbiosecurity in the food and agricultural sectors.